Saints, Sinners, and Sovereign Citizens : The Endless War over the West's Public Lands - Smith, John L., 1960- (Book collections on Project MUSE., 2020)
"Saints, Sinners, and Sovereign Citizens explores the history of grazing rights on the West's lucrative public lands and the battles between the Bureau of Land Management and ranchers for their use. The April 2014 armed standoff between Bunkerville rancher Cliven Bundy and armed militia allies against federal officers serves as the backdrop to the story of a conservative political movement and the resurgence of the radical right in the American West"--